Treatment of antebrachial and crural septic nonunion fractures in dogs using circular external skeletal fixation: a retrospective study - Cappellari, F; Piras, L; Panichi, E; Ferretti, A; Peirone, B (Veterinary and comparative orthopaedics and traumatology, 2014)
To evaluate the outcome of treatment of antebrachial and crural septic non-union fractures in dogs using circular external skeletal fixation (CESF), and to document the type and frequency of complications associated with this technique. The medical records of all dogs with infected antebrachial and crural non-union fractures treated using the methods of Ilizarov at the Department of Animal Pathology of the University of Turin between 2006 and 2011 were retrospectively reviewed. Only dogs in which radiographic and clinical assessment were available at the time of CESF removal were included in the study. Twenty-three dogs met the inclusion criteria. Twenty nonunion fractures treated with CESF healed and three did not. The latter three cases underwent amputation of the affected limb. In the 20 dogs that achieved bone union, six had minor complications and five had major complications. The mid-term outcome was judged to be excellent (n = 11), good (n = 6), fair (n = 2), or poor (n = 4). The results of this study support the use of CESF for the management of antebrachial and crural septic nonunion fractures in dogs. Union was achieved in the majority of dogs and the complication rate was acceptable, considering the severity of the nonunion fractures that were managed in this fashion.